Employer's experiences of using the supported employment model when employing persons with disabilities in the open labour market in South Africa - Makan, Reyna (Division of Occupational Therapy, 2026)
Background: Persons with disabilities (PWD) face barriers to obtaining and maintaining sustainable employment in the open labour market (OLM) in South Africa (SA) and, therefore, are under-represented in the OLM. In SA currently, there are limited services available to assist PWD in acquiring or maintaining employment in the OLM. Supported employment (SE) is a model that aims to promote employment of PWD in the OLM. Research in SA found that employers directly influence the success of employment for PWD in the OLM. Employers are uniquely positioned to create either barriers or opportunities for PWD to become integrated into South African workplaces. Employers in the OLM contribute to this factor of not employing PWD into the OLM due to the feeling of being ill-equipped and lack knowledge about disability employment. The purpose of this research was to inform practice of SE partnerships with employers to increase their capacity to use the SE model in their businesses to contribute towards sustainable employment of PWD in SA. Design: A qualitative descriptive design of inquiry was selected to describe South African employers' experiences of using the SE Model when employing PWD in OLM. Research methods: six in-depth interviews were conducted. Audio recordings were used and data was transcribed verbatim. The data was analysed through thematic analysis and represented in a report format. Findings: Four themes emerged from this research study: Facilitators in using the SE model, Challenges in using SE model, Disability attitudes shaped by the SE implementation, Employer support for SE implementation. Discussion: Employers' experiences of using the SE model were discussed in regard to the facilitators and challenges of its implementation. Employers described how the partnerships formed by the stakeholders in the SE intervention, and the role of the job coach were essential in the implementation of SE. Challenges surrounding implementation of SE were the issues around the period of re-integration for employers as well as the lack of knowledge available and inclusion in policy and legislation in SA available to support employers in the OLM on SE implementation. Employers reported an increased awareness about disability and normalised the provision of support in the workplace for employees. Employers' attitudes and understanding of disability and inclusion in the workplace were increased using the SE model. Employers' suggestions regarding needs for future implementation were made to enhance the SE implementation for future employers, such as strengthening SE partnerships with stakeholders and provision of more education and inclusion of SE in SA Legislation. This aims to inform best practice of SE in SA. The ethical considerations pertaining to this research study include following the guidelines of ethical considerations outlined in the Declaration of Helsinki (World Medical Association, 2013). This research proposal was granted ethical approval by the Human Research Ethics Committee of the Faculty of Health Sciences at the University of Cape Town. The researcher was able to maintain confidentiality can be described within enhancing practice of SE within occupational therapy (OT), for employers in SA OLM, South African government legislation and policy makers and for future research in OT. Word count: 503 Key words: Supported employment, open labour market, employment, employers, persons with disabilities qualitative research, South Africa.